2008
DOI: 10.1021/nl0733233
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effect on the Elastic Behavior of Static Bending Nanowires

Abstract: The surface effect from surface stress and surface elasticity on the elastic behavior of nanowires in static bending is incorporated into Euler-Bernoulli beam theory via the Young-Laplace equation. Explicit solutions are presented to study the dependence of the surface effect on the overall Young's modulus of nanowires for three different boundary conditions: cantilever, simply supported, and fixed-fixed. The solutions indicate that the cantilever nanowires behave as softer materials when deflected while the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
396
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(427 citation statements)
references
References 23 publications
31
396
0
Order By: Relevance
“…1,[11][12][13][14][15] Size-dependently effective Young's modulus of nanowires has been achieved, which depends on the surface elastic modulus. 1,13 In addition, molecular dynamics (MD) simulation, as a major numerical approach, has also been adopted to study the size effect of nanowires' elastic properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[11][12][13][14][15] Size-dependently effective Young's modulus of nanowires has been achieved, which depends on the surface elastic modulus. 1,13 In addition, molecular dynamics (MD) simulation, as a major numerical approach, has also been adopted to study the size effect of nanowires' elastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental resonant frequency of both fixed-fixed nanowires and cantilevered ones exhibits the same varying trend as that of the effective elastic moduli. 12 Later, the Y-L model was extended to the vibration problem of Timoshenko nanowires. 36,37 Chiu and Chen 38 further discussed the effect of the surface bending modulus on the resonant frequency of nanowires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that surface effects become significant when at least one of the dimensions of the problem is in the nanometer range. The influence of the surface on the elastic behaviour of nanowires in static bending was investigated by He and Lilley (2008) using the Young-Laplace equation. Hung and Wang (2006); Wang et al (2010b) proposed a theory of hyperelasticity accounting for surface energy effects and showed how surface tension induces a residual stress field in the bulk of nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…24,29 The reason for the significant higher values of Young's modulus of nanowires with smaller diameters is not yet entirely clear, although the surface properties and the micro-structure may play important roles, and there exists a strong size effect at the nanoscale scale. [30][31][32][33] It is known that in nanowires with tens of nanometer in diameter, the surface modulus 34 (that is determined by the surface state) is introduced, and the wires can be much more elastic 31 when compared with their bulk counterparts. With the decreasing diameter, surface effects are expected to be more significant.…”
mentioning
confidence: 99%